Field evaluation of a potential infection marker for Burgian filariasis - Noordin, Rahmah; Riazi, Mehdi; Azahari, Noor A'shikin; Huat, Lim Boon; Bujang, Abdullah; Noor, Zurainee, Mohd; Anuar, Khairul (1999)
Western blot analyses were performed on 444 serum specimens : 40 sera from microfilaraemic individuals,10 sera from elephantiasis patients, 24 treated individuals, 50 sera from residents of endemic areas without anti-filarial IgG4 "antibodies (endemic normals), 20 sera from amicrofilaraemic individuals with high anti-filarial lgG4 antibodies, 200 sera from healthy city-dwellers (non-endemic samples) and 100 sera from soil-transmitted helminth infected individuals. Phast Electrophoresis System was used to electrophorese Brugia malayi soluble adult worm antigen on 10-15% SDS-PAGE gradient gels followed by electrophoretic transfer onto PVDF membranes. Membrane strips were then successively incubated with blocking solution, human sera and monoclonal anti-human IgG4 antibody-HRP ; with adequate washings done in between each incubation steps. Luminol chemiluminescence detection was then used to develop the blots. An antigenic band with the - MW of 37 kDa was found to be consistently present in the Western blots of all microfilaraemic sera, all amicrofilaraemic sera with high titres of anti-filarial IgG4 antibodies, some treated patients and some elephantiasis patients. The antigen did not occur in immunoblots of individuals with other helminthic infections, normal endemic individuals and city dwellers. Therefore the B. malayi antigen of- MW of 3'7 kDa demonstrated specific reactions with sera of B. malayi infected individuals and thus may be useful for diagnostic application.